PENGAWETAN KAYU TISUK (Hibiscus macrophyllus Roxb.) DAN SUKUN (Artocarpus horridus Jarret.) SECARA SEL PENUH DENGAN BAHAN PENGAWET CCB DAN BORON - Sasa Abdurrohim; Jajang Nurjaman; Anne Hadiane (Jurnal Penelitian Hasil Hutan, 2003)
Tisuk (Hibiscus macrophyllus Roxb.) and sukun (Artocarpus  horridus Jarret.) trees are numerously planted by the rural community in Ciamis regency. The wood  portion of  tisuk  has been much in use for constructions material and furniture, while sukun is intended as multipurpose  plants. Due  to poor or low durability of  the wood portion in both species,  prior  to  its uses, it should be preserved or treated. Preservation  scheme for both wood species     with   particular preservatives, unfortunately, has not yet been available.  Therefore. a through   investigation is urgently required to work  out such a proper  scheme.Inherent  with  such, ninety  pieces or wood  samples, measuring of 5 by 5 by 30 cm, were  prepared from each  of both  species for the treating  trial. After being dried, the samples  pieces  were treated with CCB (copper-chrome-boron) and boron preservatives by the full-cell process. The preservatives (CCB and boron)  were each  used  in solution at  three varying  concentrations, i.e. 2, 3, and  4 percent. Initial and  final vacuums were  maintained at 600  mmHg  for 30  and 15  minutes respectively. On  the other  hand, the treating phase was employed at  three  variable pressures i.e. 4, 6, and  8 hours, for one hour.The  results revealed  that both  tisuk and  sukun were  satisfactorily treatable with CCB  solution  at 4 and  2 percent concentrations, respectively. For both CCB  treated   wood  species    used under roof and exposed to the open air without ground contact the recommended     pressures were 4 and 8 atmospheres. A schedule treatment 4 and 2 percent boron with 4 atmospheres pressure is respectively recommended  for tisuk and sukun used under roof without ground  contact.